Exploring the impacts of a nuchal cord on perinatal outcomes in vaginal delivery - Cündübey, Cevat Rifat; Ak, Mehmet; Demir, Mustafa Bertan; Dağlıtuncezdi Çam, Şeyma (The European Research Journal, 2023)
Objectives: To investigate the frequency of cord entanglement and neonatal outcomes in vaginal deliveries. Methods: A total of 24,623 patients who had vaginal delivery at at Kayseri City Hospital between July 2018 and January 2023 were included in the study. The incidence of nuchal cord was determined in the study group. The characteristics and perinatal outcomes of groups with and without nuchal cord were compared. Chi-square test was used for statistical evaluation. A p value less than 0.05 was considered significant in the evaluation. Results: The rate of cord entanglement in the neck at birth was 15.7%. There was no statistically significant difference between the infant weights, genders, maternal ages, hospitalization rates in the neonatal intensive care unit, and apgar scores at the 1st and 5th minutes of the babies included in the study. We detected amniotic fluid with meconium in 506 (13.1%) patients with a nuchal cord and 270 (1.3%) without a nuchal cord, and the difference was found to be significant. Conclusions: There is no significant relationship between vaginal deliveries with the nuchal cord and poor perinatal outcomes, except for meconium amniotic fluid. For this reason, pregnant women diagnosed with nuchal cord in the third trimester can deliver vaginally, but they should be carefully monitored in terms of meconium and related complications. However, neonates with nuchal cord do not have significantly longer neonatal hospital stays, and thus the adverse effects of nuchal cord may be transient.